Análise de variáveis que influenciam no desempenho de frenagem veicular através de ensaios baseados na metodologia Krauss - Rafael Lucas Machado Pinto (2014)
Brake systems are one of the most essential factors in a security vehicle. The process of technological developments in the car industry provided the appearance of vehicles able to achieve higher speeds and higher loads to carry increasing the demand of the standard brake systems. This work aimed to make improvements on a test bench disc brakes based on the ABNT NBR 6143:1995, in order to analyze the conditions of brake pads disc by determining the coefficient of friction and wear by bench Krauss test. The tests were conducted using a brake system of a motorcycle 125cc disc. A pair of new pads and a pair of pads half-life, and two types of brake disc: one for normal use and one with significant wear tested in two conditions of two types of brake pads were used in this system operation of the drive brake lever. The bench was instrumented, enabling the collection of data regarding certain pairs of pads and discs. The behaviors of braking as the temperature during the test, time of braking force, contact pressure and wear of the pads were raised. The friction coefficient was obtained during each braking, enabling the evaluation of the braking performance in different situations.